Pengembangan Strategi Pemasaran Berbasis Komunitas untuk Produk Kerajinan Tangan di Perumnas Monang Maning Denpasar Barat - Prihadi Dhasa Eka; Dewi Lestari; Ana Septia Rahman (Jurnal PKM Manajemen Bisnis, 2026)
Community-based marketing strategies are essential for empowering local artisans and increasing the competitiveness of handmade products in today’s market. This community service activity (PKM) aimed to strengthen the marketing capacity of craft product entrepreneurs in Perumnas Monang Maning, West Denpasar, through the development of community-based marketing strategies. The program was carried out on October 25–26, 2025, by a team of ten lecturers from Universitas Pamulang, involving twenty-four local residents as participants. The PKM activities were implemented through several stages preparation, implementation, and reporting. The implementation stage included material presentation, practical sessions, group discussions, and interactive question-and-answer sessions. The materials focused on digital marketing, branding techniques, and community collaboration in promoting local crafts. The results of the activity indicated an improvement in participants’ understanding of marketing strategy formulation and their ability to apply digital tools to promote handmade products. Participants also demonstrated increased enthusiasm in forming local marketing networks and utilizing social media for product promotion. This program contributed to enhancing community independence and sustainability in creative industry development. It is expected that continuous mentoring and digital literacy enhancement will further strengthen the marketing performance of local artisans.